DECISION SUPPORTING SYSTEM TO DECIDE THE BEST FARMING FIELD CONTROLLING EMPLOYER (PPL) IN BULELENG REGENCY USING GAP ANALYSIS METHOD - Dwi Cahyaningsih, Kadek (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
Farming is a sector that is responsible to provide people’s food needed, therefore it’s existension is really needed. Farming field controlling employer (PPL) is a person who persuades the farmers to change their old mind set and life style into the new one through information spreading process, such as training, course, admission that is related to the change and revision of how to farm well, way of farmer’s income productivity improvement, and improvement of farmer’s or people’s family prosperity. Selection of PPL-Agriculture Models are useful to give rewards to educators that can lead to the desired changes therefore conducted this study which aims to design and implement the a Decision Support System to choose the best field controlling employer in Buleleng regency. This software was done using some steps. First step is deciding maximal score for each sub aspect. Second step is counting of competency Gap mapping. Third step is deciding the score for counting result of Gap analysis. Forth step is counting and groupin the core factor and secondary factor and the final score. Laststep is rank decision. The result of this study was a decision supporting system to decide farming field controlling employer (PPL) in Buleleng regency using Gap analysis. This software was made using programming languange, Borland Delphi 2010. The test results indicate that the conceptual system has implemented a mechanism of calculationand logic mechanism in accordance with what is planned.